2019
DOI: 10.1007/s10433-019-00509-x
|View full text |Cite|
|
Sign up to set email alerts
|

Emotional intimacy and sexual well-being in aging European couples: a cross-cultural mediation analysis

Abstract: Sexual health research tends to focus on problematic aspects of sexuality. This also applies to research on sexuality in older men and women, where attention has been primarily on the negative impact of aging. To contribute to the emerging interest in positive (successful) sexual aging, we aimed to: (1) further validate a recently developed 5-dimensional measure of sexual well-being (Štulhofer et al., 2018) and (2) explore the structure of associations among emotional intimacy, frequency of sexual intercourse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 54 publications
1
21
0
3
Order By: Relevance
“…there are few studies that have used dyadic approaches to explore sexual satisfaction, particularly in older adults Štulhofer, Jurin, Graham, Janssen, & Traeen, 2019). This is regrettable, as recent evidence demonstrates how dynamics within couples can promote relationship quality and sexual satisfaction in midlife and older couples (Fisher et al, 2015;Orr et al, 2019).…”
Section: Aimsmentioning
confidence: 99%
“…there are few studies that have used dyadic approaches to explore sexual satisfaction, particularly in older adults Štulhofer, Jurin, Graham, Janssen, & Traeen, 2019). This is regrettable, as recent evidence demonstrates how dynamics within couples can promote relationship quality and sexual satisfaction in midlife and older couples (Fisher et al, 2015;Orr et al, 2019).…”
Section: Aimsmentioning
confidence: 99%
“…We found that only perceived discrepancy in sexual interest predicted sexual satisfaction in older couples (Davies et al, 1999;Sutherland et al, 2015). In addition, the finding that emotional intimacy was important for sexual satisfaction in older heterosexual couples adds to an emerging body of literature concerning diverse, intimate, and erotically flexible pathways to healthy sexual aging (Clarke, 2006;Hinchliff et al, 2018;Müller et al, 2014;Sandberg, 2013;Štulhofer et al, 2020).…”
Section: Resultsmentioning
confidence: 63%
“…Four considerable gaps in the research literature can be observed. First, despite the fact that sexual relations are inherently dualistic (Byers & Rehman, 2014; De Jong & Reis, 2014), few studies have used dyadic approaches to explore sexual satisfaction, particularly in older adults (Muise et al, 2018;Štulhofer et al, 2020). This is regrettable, as recent evidence demonstrates how dynamics within couples can promote relationship quality and sexual satisfaction in midlife and older couples (Fisher et al, 2015;Orr et al, 2019).…”
Section: Aimsmentioning
confidence: 99%
“…In their recent large-scale study, the authors observed a substantial overlap among these types of distress, with personal distress being the most prevalent and the other two types commonly cooccurring (Hendrickx et al, 2019). Considering consistent evidence on the link between emotional closeness, relationship quality, relationship satisfaction, and sexual functioning in older age (Fisher et al, 2015;Galinsky & Waite, 2014;Hinchliff et al, 2018;Štulhofer, Jurin, Graham, Janssen, & Traeen, 2019), the interrelatedness between personal, partner, and relational sexual distress is not surprising. As highlighted in a recent qualitative study (Hinchliff et al, 2018), the link between relationship quality and sexual distress is not unidirectional.…”
Section: Aging and Sexual Distressmentioning
confidence: 96%